1987
DOI: 10.1093/iat/12.1.244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insecticides for Control of Tarnished Plant Bug on Cotton in Mississippi, 1986

Abstract: Sixteen insecticide treatments were evaluated on 4 row (40 inch centers) by 49 ft long plots arranged in a randomized complete block design with 4 replications at the Delta Branch Experiment Station, Stoneville, MS. Plots were planted 6 May in a 4 row skip pattern with mustard planted (23 Apr) in the center two rows of the 4 row skip to encourage plant bug establishment. Plots were delimited by alleys formed by cultivating across the rows between plots with a 4 row cultivator. The mustard was cut on 12 Jun and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Reed et al. (1999) reported that pyrethroids provided 94% control of TPBs in 1982, 73% in 1986, and 56% in the late 1990s. The first documented cases of pyrethroid resistance occurred by the mid‐1990s in the Delta area of Arkansas, Louisiana, and the Mississippi and became widespread by the turn of the century (Snodgrass, 1996b; Snodgrass & Scott, 1999; Snodgrass & Scott, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reed et al. (1999) reported that pyrethroids provided 94% control of TPBs in 1982, 73% in 1986, and 56% in the late 1990s. The first documented cases of pyrethroid resistance occurred by the mid‐1990s in the Delta area of Arkansas, Louisiana, and the Mississippi and became widespread by the turn of the century (Snodgrass, 1996b; Snodgrass & Scott, 1999; Snodgrass & Scott, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the efficiency of OPs declined sharply since 1985 in Mississippi and other states (Reed et al. , 1999), resistance to multiple OP insecticides was first recorded in 2001 (Snodgrass & Scott, 2002). Acephate, an OP insecticide, was one of the most commonly used insecticides for controlling TPB in cotton in Mississippi Delta region, while resistance to acephate at concentrations high enough to cause control failures in the field were widespread in the Mid‐South by the late 2000's (Snodgrass et al.…”
Section: Introductionmentioning
confidence: 99%